Book review: Bringing The Right Arm Back: A Journey in Sufi Corporate Leadership - Kamel, Sherif (Journal of management, spirituality & religion, 2026)
Bringing The Right Arm Back: A Journey in Sufi Corporate Leadership presents a distinctive approach to leadership, rooted in Sufi spirituality and Islamic ethical traditions, and validated within IBAG, a prominent Egyptian financial services company. It introduces the Sufi Corporate Leadership Model (SCLM), which combines spiritual Corporate Self (CNafs), Corporate Faith (CIman), Corporate Excellence (CIhsan), and Corporate Submission (CIslam) - four interdependent dimensions that embed spiritual principles into organizational life, forming a practical framework for leadership. The author focuses on Sufism from the standpoint of transforming the individual at the most fundamental level, where Sufism is the spiritual side of Islam. Using a mix of Strauss's Grounded theory, one-case, intrinsic study, and qualitative cross-sectional and semi-structured interviews, coupled with a narrative that reflects a personal journey and life experience, the author suggests that Sufi-inspired leadership can build trust, resilience, and high performance in diverse, multicultural business settings. This review evaluates the book's theoretical insights, empirical foundation, practical significance, and educational value, situating it within the broader literature on spiritual, servant, and ethical leadership. The analysis emphasizes the model's originality, its alignment with current calls for humane management, and its limitations in terms of generalizability and empirical rigor. The review ends with implications for research, management practice, and business education, particularly in emerging markets and diverse societies.